Sex differences and rehabilitation needs after hospital discharge for COVID-19: an Italian cross-sectional study - Luca Braglia; Monica Denti; Stefania Fugazzaro; Stefania Costi; Carlotta Mainini; Monia Allisen Accogli; Ginevra Bedogni; Daniele Ghizzoni; Anna Bertolini; Otmen Esseroukh; Cecilia Gualdi; Margherita Schiavi (BMJ Open)
Objectives COVID-19 can result in persistent symptoms leaving potential rehabilitation needs unmet. This study aims to describe persistent symptoms and health status of individuals hospitalised for COVID-19 according to the International Classification of Functioning, Disability and Health domains of impairments, limitations in activity, and participation restrictions.Design Cross-sectional study consisting in a telephone interview 3 months after hospital discharge.Setting This study was conducted during the first peak of the COVID-19 pandemic by the Local Health Authority of Reggio Emilia (Italy).Participants Adult individuals discharged from hospital between April and June 2020 after COVID-19. Exclusion criteria: hospitalisation for reasons other than COVID-19, inability to participate in the study, concomitant acute or chronic conditions causing disability.Primary and secondary outcome measures We assessed: dyspnoea (Medical Research Council), fatigue (Fatigue Severity Scale), mood disturbances (Hospital Anxiety and Depression Scale), limitations in activity (Barthel Index) and participation restrictions (Reintegration to Normal Living Index). We also collected data on sociodemographic characteristics, health status prior to COVID-19, COVID-related clinical manifestations and hospital care pathway up to discharge, rehabilitation interventions, accidental falls and emergency room access.Results 149 participants (men, 62%; average age 62 (±11) years) were enrolled, 35 of which (23%) were admitted to the intensive care unit (ICU) while hospitalised. Three months after hospital discharge, nearly half of the participants still suffered from dyspnoea (44%) or fatigue (39%). Almost all individuals (91.2%) recovered a good level of independence in activity of daily living, but 76% still suffered participation restrictions. Female sex was significantly associated with worse outcomes for all symptoms.Conclusions Individuals who had moderate or severe COVID-19 may perceive persistent symptoms which may result in reduced social participation. Sex differences should be monitored, as women may recover more slowly than men.Trial registration number NCT04438239.